Regional growth patterns in Sweden - a search for hot spots - Johan Lundberg (European Regional Science Association (ERSA), 2002)
This paper gives an exploratory description of the regional growth pattern in Sweden during the period 1981-1999. The main issue is to test the hypothesis that municipalities with higher average income growth and net migration rates are more clustered that could be caused by pure chance. The paper is purely descriptive and we make use of statistical tests for spatial clustering as well as maps to identify what we reefer to as 'regional hot spots'. Our results are however very sensitive for the specification of the weights matrix.
Keywords: 330